2011
DOI: 10.1258/ijsa.2011.010541
|View full text |Cite
|
Sign up to set email alerts
|

Oral sex practices, oral human papillomavirus and correlations between oral and cervical human papillomavirus prevalence among female sex workers in Lima, Peru

Abstract: Summary Few data exist on oral human papillomavirus (HPV) prevalence in female sex workers (FSWs). Information regarding oral sex practices of 185 Peruvian FSWs, 18–26 years of age, was obtained via survey and compared with HPV testing results of oral rinse samples. Oral HPV prevalence was 14/185 (7.6%); four (28.9%) HPV genotypes were carcinogenic. One hundred and eighty-two participants reported having had oral sex; 95% reported condom use during oral sex with clients and 9.5% with partners. Women who had or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 25 publications
2
26
1
Order By: Relevance
“…The present study aimed at assessing the prevalence of HPV infection at cervical, oropharyngeal and anal sites of sex workers as well as exploring association between sexual behaviour, condom usage and HPV positivity as well as investigating awareness of the prevention of HPV and other STDs of this HR population. This study's results were consistent with previous papers reporting a significantly higher prevalence of HPV infection among FSWs than that of the general population (Kjaer et al 2000;Ford et al 2003;Canadas et al 2004;Mak et al 2004;del Amo et al 2005;Ortiz et al 2006;Sultana et al 2008;Brown et al 2011;Shikova et al 2011) as the HPV DNA was detected in at least one location in a great majority (82.4%) of the FSWs and less than half of the control women (46.2%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study aimed at assessing the prevalence of HPV infection at cervical, oropharyngeal and anal sites of sex workers as well as exploring association between sexual behaviour, condom usage and HPV positivity as well as investigating awareness of the prevention of HPV and other STDs of this HR population. This study's results were consistent with previous papers reporting a significantly higher prevalence of HPV infection among FSWs than that of the general population (Kjaer et al 2000;Ford et al 2003;Canadas et al 2004;Mak et al 2004;del Amo et al 2005;Ortiz et al 2006;Sultana et al 2008;Brown et al 2011;Shikova et al 2011) as the HPV DNA was detected in at least one location in a great majority (82.4%) of the FSWs and less than half of the control women (46.2%).…”
Section: Discussionsupporting
confidence: 92%
“…; Brown et al . ; Shikova et al . ) as the HPV DNA was detected in at least one location in a great majority (82.4%) of the FSWs and less than half of the control women (46.2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this hypothesis, Brown et al. reported that only 7.6% of women who practiced oral sex had oral HPV. The absence of HPV was higher in women who practiced oral sex than those who did not (33.8% vs. 20%), result similar to that shown by Giraldo et al.…”
Section: Discussionmentioning
confidence: 87%
“…For example, the prevalence of oncogenic HPV in the oral cavity is significantly lower than in the cervix, even among women with similar histories of oral and vaginal sexual activity [4,5]. Furthermore, the relative risk of anogenital HIV-1 transmission is three times higher than oral HIV transmission [6].…”
Section: Introductionmentioning
confidence: 99%